Baicalein reduces β‐amyloid and promotes nonamyloidogenic amyloid precursor protein processing in an Alzheimer's disease transgenic mouse model. Issue 9 (17th May 2013) - Zhang, She‐Qing; Obregon, Demian; Ehrhart, Jared; Deng, Juan; Tian, Jun; Hou, Huayan; Giunta, Brian; Sawmiller, Darrell; Tan, Jun
<x xml:space="preserve">Abstract</x> Baicalein, a flavonoid isolated from the roots of Scutellaria baicalensis, is known to modulate γ‐aminobutyric acid (GABA) type A receptors. Given prior reports demonstrating benefits of GABAA modulation for Alzheimer's disease (AD) treatment, we wished to determine whether this agent might be beneficial for AD. CHO cells engineered to overexpress wild‐type amyloid precursor protein (APP), primary culture neuronal cells from AD mice (Tg2576) and AD mice were treated with baicalein. In the cell cultures, baicalein significantly reduced the production of β‐amyloid (Aβ) by increasing APP α‐processing. These effects were blocked by the GABAA antagonist bicuculline. Likewise, AD mice treated daily with i.p. baicalein for 8 weeks showed enhanced APP α‐secretase processing, reduced Aβ production, and reduced AD‐like pathology together with improved cognitive performance. Our findings suggest that baicalein promotes nonamyloidogenic processing of APP, thereby reducing Aβ production and improving cognitive performance, by activating GABAA receptors. © 2013 Wiley Periodicals, Inc.